PENGARUH HARGA PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN KM. DOROLONDA PT.PELNI ( JAKARTA-MAKASSAR ) - Salman Paludi; Pamuji Gesang Raharjo; Ekaningtyas Saefani Sholekhah (Eduturisma, 2018)
The research was conducted on passenger of PT.Pelni KM.Dorolonda (JakartaMakassar. The purpose of the research is to determine how the price, promotion, and service quality are able to influence to customer satisfaction in ship PT.Pelni KM.Dorolonda. The data used in this study are primary with technique of determining samples with certain considerations given to a sample of 100 passengers PT.Pelni KM.Dorolonda with purposivesampling method. The variable in this study is the price (X1), promotion(X2), service quality(X3) and customer satisfaction(Y).In this study the authors used quantitative methods, by analyzing the data with the help of statistical software SPSS version 20.00. The analytical method used is multiple linear regression. The result of this analysis states that the price, promotion and service quality simultaneously have a significant influence on customer satisfaction at KM.Dorolonda. partially the price (X1), promotion(X2), and the service quality (X3) have a significant influence on customers satisfaction (Y) of PT.Pelni KM.Dorolonda. Based on the coefficient of determination value R of 0,806 or 64,96% of customer satisfaction (Y) can be explained by the variable price (X1), promotion(X2), service quality (X3) the remaining 35,04% are influenced by other variables that are not used in this research